Identifying the mechanisms of patient-centred communication in secure messages between clinicians and cancer patients - Aantaki Raisa; Jordan M. Alpert; Carma L. Bylund; Samah Jarad-Fodeh (PEC Innovation, 2023)
Objective: Identify how patients and clinicians incorporate patient-centered communication (PCC) within secure messaging. Methods: A random sample of 199 secure messages from patient portal communication between patients and clinicians were collected and analyzed. Via manual annotation, the task of tagging target words/phrases in text, we identified five components of PCC: information giving, information seeking, emotional support, partnership, and shared decision-making. Textual analysis was also performed to understand the context of PCC expressions within messages. Results: Information-giving was the predominant (n = 346, 68.1%) PCC category used in secure messaging, more than double of the other four PCC codes, information-seeking (n = 82, 16.1%), emotional support (n = 52, 10.2%), shared decision making (n = 5, 1.0%), combined. The textual analysis revealed that clinicians informed patients about appointment reminders and new protocols while patients reminded clinicians about upcoming procedures and outcomes of test results conducted by other clinicians. Although less common, patients expressed statements of concern, uncertainty, and fear; enabling clinicians to provide support. Conclusion: Secure messaging is mainly used for exchanging information, but other aspects of PCC emerge using this channel of communication. Innovation: Meaningful discussions can occur via secure messaging, and clinicians should be mindful of incorporating PCC when communicating with patients through secure messaging.